The Effect of Tuina Massage in Improving Diet in Underweight Children Under Five in 2024 - Nofa Anggraini; Cica Repita; Devi Apriliani; Dinda Amalia; Fatma Tuzakia; Lumyati; Risna Dewi; Sri Wahyuni (Jurnal Penelitian Pendidikan IPA, 2025)
Underweight among children under five remains a major nutritional problem that affects physical growth and cognitive development. One of the non-pharmacological approaches to improve appetite and digestion is Tuina massage, a traditional Chinese therapy that stimulates specific meridian points related to the digestive system. However, empirical evidence on its effectiveness in improving dietary patterns among underweight children is still limited. This study aimed to determine the effect of Tuina massage on improving eating patterns among underweight children under five years old in 2024. This research employed a pre-experimental design with a one-group pretest–posttest approach conducted from October to December 2024 across seven health centers in Banten Province, including Cisimeut Health Center, Azzahra Maja Primary Clinic, Pasar Baru Health Center, Tambak Menteng Hospital, Cipanas Inpatient Health Center, and two private midwife clinics (PMB Desy Sri Latipah and PMB Iis Parhati). The Wilcoxon signed-rank test was used to analyze pretest and posttest differences in dietary patterns. Statistical analysis showed a significant improvement in dietary patterns after Tuina massage intervention (p < 0.05) across all study sites. Tuina massage effectively enhances eating behavior among underweight children and may serve as a complementary, non-pharmacological therapy for improving nutritional intake in early childhood.